Hurricanes: intertemporal trade and capital shocks - Bluedorn, J (University of Oxford, 2005)
Hurricanes in the Caribbean and Central America represent a natural experiment to test the intertemporal approach to current account determination. The intertemporal approach allows for the possibility of intertemporal trade, via international borrowing. Previous tests of intertemporal current account (ICA) models have typically relied upon the identification of shocks in a VAR framework with which to trace the current account response. Hurricane shocks represent exactly the kind of temporary, country-specific shock required by the theory, allowing for the intertemporal current account response to be estimated without recourse to a VAR shock decomposition. Using data on the economic damages attributable to a hurricane, I estimate the economy's response to a hurricane-induced capital shock within a fixed effects panel model. The current account response qualitatively conforms to the S-shaped response predicted by the theory, indicating that countries are engaging in intertemporal trade. However, the exact timing and magnitude of the response differs from a standard ICA model's smooth behavior. A hurricane which destroys capital valued at one year's GDP pushes the current account over GDP into deficit by 5 percentage points initially. 3-8 years after such a hurricane, the current account over GDP moves into surplus at 2.7 percentage points.